2019
DOI: 10.2169/internalmedicine.3131-19
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Ileocolonic Varices Coexisting with a Colon Polyp Treated Successfully by Endoscopy: A Case Report and Literature Review

Abstract: Colonic varices are usually associated with portal hypertension. Idiopathic colonic varices are extremely rare. A 68-year-old man with a positive fecal occult blood test result underwent colonoscopy. We detected idiopathic ileocolonic varices and a coexisting ascending colon polyp. While reviewing the literature, we found cases of biopsies and polypectomies resulting in significant bleeding. We herein report a case of idiopathic ileocolonic varices coexisting with a colon polyp treated successfully by endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Idiopathic colonic and small bowel varices in the absence of portal hypertension are exceedingly rare, with less than 40 cases reported in the literature 1. Most patients with idiopathic colonic varices present with massive hematochezia; however, they may be found during routine screening colonoscopy or as part of work-up for iron deficiency anemia, as was seen in this case 2. Colonic varices are typically the result of increased portal pressure, usually secondary to cirrhosis.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Idiopathic colonic and small bowel varices in the absence of portal hypertension are exceedingly rare, with less than 40 cases reported in the literature 1. Most patients with idiopathic colonic varices present with massive hematochezia; however, they may be found during routine screening colonoscopy or as part of work-up for iron deficiency anemia, as was seen in this case 2. Colonic varices are typically the result of increased portal pressure, usually secondary to cirrhosis.…”
mentioning
confidence: 68%
“… 1 Most patients with idiopathic colonic varices present with massive hematochezia; however, they may be found during routine screening colonoscopy or as part of work-up for iron deficiency anemia, as was seen in this case. 2 Colonic varices are typically the result of increased portal pressure, usually secondary to cirrhosis. The diagnosis of idiopathic colonic varices is made by excluding portal hypertension.…”
Section: Case Reportmentioning
confidence: 99%
“…While stalk transection of large pedunculated lesions has been well documented in the literature, a combinatorial approach involving band ligation of associated stalk varices is altogether novel [ 1 , 2 ]. A literature review identified a similar case involving band ligation of adjacent cirrhosis-related varices in a unique patient undergoing rectal endoscopic submucosal dissection [ 3 ].…”
mentioning
confidence: 99%